Financial conflicts of interest in systematic reviews: associations with results, conclusions, and methodological quality - Hansen, Camilla (Cochrane Database Syst Rev, 2019)
BACKGROUND: Financial conflicts of interest in systematic reviews (e.g. funding by drug or device companies or authors' collaboration with such companies) may impact on how the reviews are conducted and reported. OBJECTIVES: To investigate the degree to which financial conflicts of interest related to drug and device companies are associated with results, conclusions, and methodological quality of systematic reviews. SEARCH METHODS: We searched PubMed, Embase, and the Cochrane Methodology Register for studies published up to November 2016. We also read reference lists of included studies, searched grey literature sources, and Web of Science for studies citing the included studies. SELECTION CRITERIA: Eligible studies were studies that compared systematic reviews with and without financial conflicts of interest in order to investigate differences in results (estimated treatment effect and frequency of statistically favourable results), frequency of favourable conclusions, or measures of methodological quality of the review (e.g. as evaluated on the Oxman and Guyatt index). DATA COLLECTION AND ANALYSIS: Two review authors independently determined the eligibility of studies, extracted data, and assessed risk of bias. We synthesised the results of each study relevant to each of our outcomes. For meta‐analyses, we used Mantel‐Haenszel random‐effects models to estimate risk ratios (RR) with 95% confidence intervals (CIs), with RR > 1 indicating that systematic reviews with financial conflicts of interest more frequently had statistically favourable results or favourable conclusions, and had lower methodological quality. When a quantitative synthesis was considered not meaningful, results from individual studies were summarised qualitatively. MAIN RESULTS: Ten studies with a total of 995 systematic reviews of drug studies and 15 systematic reviews of device studies were included. We assessed two studies as low risk of bias and eight as high risk, primarily because of risk of confounding. The estimated treatment effect was not statistically significantly different for systematic reviews with and without financial conflicts of interest (Z‐score: 0.46, P value: 0.64; based on one study of 14 systematic reviews which had a matched design, comparing otherwise similar systematic reviews). We found no statistically significant difference in frequency of statistically favourable results for systematic reviews with and without financial conflicts of interest (RR: 0.84, 95% CI: 0.62 to 1.14; based on one study of 124 systematic reviews). An analysis adjusting for confounding due to methodological quality (i.e. score on the Oxman and Guyatt index) provided a similar result. Systematic reviews with financial conflicts of interest more often had favourable conclusions compared with systematic reviews without (RR: 1.98, 95% CI: 1.26 to 3.11; based on seven studies of 411 systematic reviews). Similar results were found in two studies with a matched design, which therefore had a reduced risk of confounding. Systematic reviews with financial conflicts of interest tended to have lower methodological quality compared with systematic reviews without financial conflicts of interest (RR for 11 dimensions of methodological quality spanned from 1.00 to 1.83). Similar results were found in analyses based on two studies with matched designs. AUTHORS' CONCLUSIONS: Systematic reviews with financial conflicts of interest more often have favourable conclusions and tend to have lower methodological quality than systematic reviews without financial conflicts of interest. However, it is uncertain whether financial conflicts of interest are associated with the results of systematic reviews. We suggest that patients, clinicians, developers of clinical guidelines, and planners of further research could primarily use systematic reviews without financial conflicts of interest. If only systematic reviews with financial conflicts of interest are available, we suggest that users read the review conclusions with skepticism, critically appraise the methods applied, and interpret the review results with caution.